Improving Quality of Learning with Syariah Accounting Mind Mapping Method in Accounting Program at Universitas Negeri Medan - Saparuddin Siregar; Anggriyani Anggriyani; Nasirwan Nasirwan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
Problems in this study is the result of studying the Syariah Accounting courses that students have not showed significant results. The acquisition of student value is Relatively unfavourable because of the lack of precise learning method that has been used, Thus affecting the low of students' reasoning. Therefore, Researchers offer Mind Mapping as a solution in improving student achievement. Mind Mapping aims: (1) To know Whether Mind Mapping in KDBK Syariah Accounting feasible to be used in the student. (2) To direct and guide lecturers in improving the quality of learning through Mind Mapping. (3) Become a training tool for Reviews their lecturers to publish research results in scientific journals, both locally and Nationally accredited. This study will run and be done within 5 years of the whole course of KDBK Accounting Sharia. The subjects of this study are students majoring in accounting who take Syariah Accounting courses. Data analysis in this research using quantitative descriptive analysis. All the data collected is Analyzed by descriptive statistical techniques that are quantitatively segregated by category to sharpen judgments in drawing Conclusions. The result shows that Mind Mapping method is very suitable for students in accounting KDBK Syariah and proven to improve the quality of learning and can be a reference in the research result of lecturer in the scientific journal. There is also an invention where there are differences in students' understanding of the Syariah Accounting courses using Mind Mapping between Reviews those methods and Reviews those that do not